(untitled) (Indonesian Tax Justice Review, 2025)
Recent Indonesian Supreme Court rulings have addressed the taxation of cross-border digital services. This paper analyzes these decisions to assess their implications for tax justice and digital economy governance. Using jurisprudential analysis, the study examines interpretations of permanent establishment and source rules. The findings indicate evolving judicial recognition of digital economic presence. The global contribution of this study lies in offering early judicial insights from a developing country confronting digital taxation challenges. Indonesia’s experience informs international debates on adapting tax concepts to digital business models and contributes to global tax justice scholarship.